Ivermectin and doxycycline treatments against Onchocerciasis: Adaptations and impact among semi-nomadic population in Massangam Health District, Cameroon. - Rogers Nditanchou; Ruth Dixon; Kareen Atekem; Benjamin Biholong; Aude Wilhelm; Richard Selby; Joseph Oye; Joseph Kamgno; Daniel Boakye; Elena Schmidt; Laura Senyonjo (Public Library of Science (PLoS), 2023)
We trialed strategies to reach semi-nomadic population with interventions targeting onchocerciasis including a combination of community knowledge and Geographical Information System (GIS) technology; nomad-specific sensitization; and mobile outreach. The interventions included ivermectin (ivm) mass drug administration (MDA) and treating infected individuals (found upon skin snip microscopy test) with doxycycline for 35 days. Microscopy-negative snips were further tested by Polymerase Chain Reaction (PCR). After 8 months, individuals immigrating or emigrating constituted 47% of the initial population; 59% of individuals not born in the area have immigrated during the last five years; 28% (age>9) reportedly never taken ivm; 72% (compared to 51% previously) of eligible population (age ≥ 5 years) took ivm; and 47% (age > 8, not pregnant, not breastfeeding, not severely ill,) participated in the test. A high prevalence of onchocerciasis,15.1%, was found upon microscopy & PCR test; 9/10 tested by skin snip microscopy and PCR at follow-up were all negative. Microfilaria prevalence and intensity upon skin snip microscopy reduced significantly from baseline following the intervention (8.9% to 4.1%, p = 0.032; 0.18 to 0.16, p = 0.013, respectively). The strategies considerably increased reach to nomadic camps. Treating with doxycycline in combination with ivm is feasible and has led to a significant reduction in infection level within one year among the semi-nomads. Being potentially curative in one intervention round, this combination should be considered for population group faced with challenges of achieving adequate coverage and adhesion to ivm MDA over prolonged period (>10 years).